2020
DOI: 10.3847/1538-4365/ab7230
|View full text |Cite
|
Sign up to set email alerts
|

Scaling K2. I. Revised Parameters for 222,088 K2 Stars and a K2 Planet Radius Valley at 1.9 R

Abstract: Previous measurements of stellar properties for K2 stars in the Ecliptic Plane Input Catalog (EPIC;Huber et al. 2016) largely relied on photometry and proper motion measurements, with some added information from available spectra and parallaxes. Combining Gaia DR2 distances with spectroscopic measurements of effective temperatures, surface gravities, and metallicities from the Large Sky Area Multi-Object Fibre Spectroscopic Telescope (LAMOST) DR5, we computed updated stellar radii and masses for 26,838 K2 star… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 95 publications
(59 citation statements)
references
References 91 publications
1
57
1
Order By: Relevance
“…8, we show the distribution of planet-candidate radii from our K2-HERMES sample. Our sample, although smaller than the surveys conducted by Fulton et al (2017) and Hardegree-Ullman et al (2020), also sees a drop off in exoplanetary candidates and confirmed exoplanets centred around 1.8R ⊕ . Hardegree-Ullman et al (2020) in particular showed that K2 planet candidates were depleted within a radius gap centred at 1.9 R ⊕ .…”
Section: P L a N E T C A N D I Dat E Pa R A M E T E R Scontrasting
confidence: 48%
“…8, we show the distribution of planet-candidate radii from our K2-HERMES sample. Our sample, although smaller than the surveys conducted by Fulton et al (2017) and Hardegree-Ullman et al (2020), also sees a drop off in exoplanetary candidates and confirmed exoplanets centred around 1.8R ⊕ . Hardegree-Ullman et al (2020) in particular showed that K2 planet candidates were depleted within a radius gap centred at 1.9 R ⊕ .…”
Section: P L a N E T C A N D I Dat E Pa R A M E T E R Scontrasting
confidence: 48%
“…If a significant portion of the sample parameters are inaccurate, we will under-or overestimate the difficulty of detecting planets, and therefore bias the occurrence measurements. To minimize this effect, we use the stellar parameters provided by Hardegree-Ullman et al (2020), as this provides the most uniform and up-to-date stellar parameters for K2. Using Gaia DR2 and LAMOST spectroscopic data, this sample significantly reduces the uncertainty in stellar radius measurements compared to measurements derived primarily by photometry (Huber et al 2016).…”
Section: K2 Stellar Selectionmentioning
confidence: 99%
“…Of these stars, only 865 rely on parameters from Huber et al (2016). The remaining 8392 stars use parameters derived by Hardegree-Ullman et al (2020). Finally, we calculate the two quadratic limb-darkening values for each target, using the ATLAS model coefficients for the Kepler bandpasses tabulated by Claret & Bloemen (2011).…”
Section: K2 Stellar Selectionmentioning
confidence: 99%
“…Such extreme environments can radically alter planetary evolution, potentially driving atmospheric mass loss via thermal escape (e.g., Tian 2015; Owen 2019). Mass loss can in turn leave substantial imprints on observed planetary statistics, such as the dearth of planets between 1.5 and 2 Earth radii (the "radius gap" or "evaporation valley") and the so-called "Neptune desert" in the radius-period plane (Lopez & Fortney 2013;Owen & Wu 2013Fulton et al 2017;Fulton & Petigura 2018;van Eylen et al 2018;Cloutier & Menou 2020;Hardegree-Ullman et al 2020). Over the past two decades, most measurements of mass-loss rates for close-in planets have been conducted at ultraviolet wavelengths, with Lyα detections for HD 209458b (Vidal-Madjar et al 2003), HD 189733b (Lecavelier Des Etangs et al 2010;Lecavelier des Etangs et al 2012), GJ 436b (Kulow et al 2014;Ehrenreich et al 2015;Lavie et al 2017), and GJ 3470b (Bourrier et al 2018); tentative/marginal signals for TRAPPIST-1b and c (Bourrier et al 2017a), Kepler-444e and f (Bourrier et al 2017b), and K2-18b (dos Santos et al 2020); and nondetections for 55 Cnc e (Ehrenreich et al 2012), HD 97658b (Bourrier et al 2017c), GJ 1132 b (Waalkes et al 2019), and π Men c (García Muñoz et al 2020).…”
Section: Introductionmentioning
confidence: 99%